North-South Trade : Is Africa Unusual? - Coe, David; Hoffmaister, Willy (Washington, D.C. : International Monetary Fund, 1998)
We estimate a gravity model to address the question of whether Africa's bilateral trade with industrial countries is 'unusual' compared with other developing country regions. Our main finding is that the unusually low level of African trade is explained by economic size, geographical distance, and population. This result holds after controlling for a country's access to the sea, composition of exports, linguistic ties with industrial countries, and trade policies. If anything, the average African country tends to 'overtrade' compared with developing countries in other regions, although the degree to which Africa overtrades has steadily declined over the past two-and-one-half decades.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet